LEXICAL AND GRAMMATICAL PROPERTIES OF LATIN SUFFIXES IN MEDICAL TERMINOLOGY (International journal of artificial intelligence, 2026)
The article discusses the lexical and grammatical features of derivational suffixes in the Latin language that create different meanings, illustrated through examples. Terms containing such suffixes constitute a relatively small part of medical terminology. These suffixes are attached to the root of a word and express various meanings. In Latin, there are noun-forming and adjective-forming suffixes. Knowledge of these derivational and semantic suffixes is important for the easy formation and translation of medical terms.